2021
DOI: 10.1097/coh.0000000000000708
|View full text |Cite
|
Sign up to set email alerts
|

A new paradigm for antiretroviral delivery: long-acting cabotegravir and rilpivirine for the treatment and prevention of HIV

Abstract: Purpose of review Cabotegravir (CAB) and rilpivirine (RPV) is the first long-acting injectable antiretroviral therapy (ART) option approved for virologically suppressed adults with HIV-1. In addition, long-acting CAB is a promising agent for HIV preexposure prophylaxis (PrEP). This review focuses on phase 3 clinical trial results and implementation considerations for these long-acting ART and PrEP strategies. Recent findings Long-acting CAB and RPV administered every 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 34 publications
(64 reference statements)
1
23
0
1
Order By: Relevance
“…Likewise, the FDA and insurance providers have set similar criteria for LAI-ART eligibility–patients must be virologically suppressed on the current oral regimen, have VL < 50 copies/ml, and have no reported history of virologic failure [ 7 , 16 ]. Based on the general perspective that LAI-ART is an effective tool for improving adherence for individuals like those presented in this case series, and considering the high levels of reported adherence and acceptability of the LAI-ART, such limiting criteria potentially exclude those that need the drug the most [ 17 , 18 ]. These cases also highlight that in some patients, LAI-ART have a potential benefit of reducing pill burden in patients who may still require oral medications.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, the FDA and insurance providers have set similar criteria for LAI-ART eligibility–patients must be virologically suppressed on the current oral regimen, have VL < 50 copies/ml, and have no reported history of virologic failure [ 7 , 16 ]. Based on the general perspective that LAI-ART is an effective tool for improving adherence for individuals like those presented in this case series, and considering the high levels of reported adherence and acceptability of the LAI-ART, such limiting criteria potentially exclude those that need the drug the most [ 17 , 18 ]. These cases also highlight that in some patients, LAI-ART have a potential benefit of reducing pill burden in patients who may still require oral medications.…”
Section: Discussionmentioning
confidence: 99%
“…In discussing options for ART, NPs should employ shared decision making to learn about and respect patients' values and preferences and provide potential alternatives to the route of medication administration where appropriate. 19,20 ■ Advantages Advantages of prescribing an ER injectable ART over oral includes a less frequent dosing schedule, decreased pill burden, convenience, and avoidance of DDIs at the level of the GI tract. 14,20 Additionally, injectable ART administered in a clinic can provide privacy in that patients do not need to store HIV medications at home.…”
Section: ■ Barriers To Art Adherencementioning
confidence: 99%
“…19,20 ■ Advantages Advantages of prescribing an ER injectable ART over oral includes a less frequent dosing schedule, decreased pill burden, convenience, and avoidance of DDIs at the level of the GI tract. 14,20 Additionally, injectable ART administered in a clinic can provide privacy in that patients do not need to store HIV medications at home. 21 A study on patient perception found that 57% of participants were likely to accept long-acting injectable ART.…”
Section: ■ Barriers To Art Adherencementioning
confidence: 99%
See 1 more Smart Citation
“…Antivirals to treat HIV exist, but it has been reported that some drugs, such as ritonavir or efavirenz, can cause dyslipidemia and atherosclerosis [ 90 , 91 ]. Pre-exposure prophylaxis (PrEP) treatment was the only option to prevent HIV infection, but the U.S., the FDA has recently approved the first injection drug Apretude to prevent HIV infection [ 92 , 93 , 94 , 95 , 96 ]. Additionally, it has been reported that various antiretroviral drug treatments including Ritonavir, Saquinavir, Nelfinavir, Indinavir, Efavirenz, and Tenofovir alafenamide can increase the levels of human blood lipids and the incidence of atherosclerosis [ 97 ].…”
Section: Human Immunodeficiency Virusmentioning
confidence: 99%